МЕТОД ІМІТАЦІЇ РІВНОМІРНОГО РУХУ ОПТИКО-ЛОКАЦІЙНОГО ПРИСТРОЮ - Сантоній, В. І.; Іванченко, І. О.; Будіянська, Л. М.; Лепіх, Я. І. (Сенсорна електроніка і мікросистемні технології, 2019)
The aim of the work is to develop a method of physico-mathematical modeling of opticalelectronic systems functioning conditions that solve the problem of reducing the time and cost of experimental studies. The main idea of the simulation method was to replace the uniform rectilinear motion of an optical-location device (OLD) with respect to the object under investigation by scanning its field of view along a fixed MS. Physical modeling of the OLD uniform motion was carried out by scanning the radiation along a reflecting surface bent according to the Archimedes’ helix shape. The mechanical and mirror scanning methods schemes of radiation by a spiral MD are presented. The criteria for the suitability of scanning methods for various types of OLD depending on the radiation pattern of the receiving-transmitting unit, the scanner’s mirror size and the angle of its installation, as well as the range of simulated driving speeds are indicated. A mathematical model of the simulation method, which determines the dependence of the OLD amplitude of the reflected radiation on the distance (the law of squares of distances) and the angle of incidence of the radiation on the MD (Lambert’s law), was developed. A functional analysis is carried out and the calculation results of the dependence on the MD radiation angle incidence on the polar radius rotation angle, which determines the simulated range value, are presented. The variation limits of the distance measuring relative error from 20 to 9%, introduced by the variable angle of radiation reflection in the range of the radiation incidence angle of 0 ... π, respectively, are established. The analytical expression for the angular correction of the reflected radiation amplitude, which compensates for the angular error of the simulation method, is given. The field and simulation measurements results of the OLD base model distance characteristics based on an optocoupler LED AL107 - FD155K photodiode are presented. Comparison of the results showed ascent at small distances with a tendency to decrease with increasing distance. In this case, the absolute measurement error is significantly reduced as a result of the calculated angular correction. The average value of the simulation measurements relative error was ~ 20%, and taking into account the angular correction - ~ 15%. The work results showed the applicability of the method of OLD uniform rectilinear motion imitation using a spiral MS.